Mountain neurology. Issue 5 (8th June 2019) - Dekker, Marieke Cornelia Johanna; Wilson, Mark H; Howlett, William Patrick
Abstract : Mountain climbers may develop specific illnesses that largely depend on the altitude reached and the rate of ascent. The popularity of travel to high altitude destinations, extreme tourist activities and mountain climbing means that neurologists in low-altitude countries are increasingly likely to encounter neurological problems and disorders in people exposed to high altitude. Additionally, they may have to advise patients with pre-existing neurological conditions on the risks of ascent to altitude. This article focuses on neurological-related high-altitude illnesses: acute mountain sickness and high-altitude cerebral oedema, as well as high-altitude retinopathy and other neurological disorders. This overview combines current understood pathogenesis with the experience of managing altitude-related illness at the foot of Mount Kilimanjaro in northern Tanzania, the tallest free-standing mountain in the world.